BiOCl/UiO‐66 composite with enhanced performance for photo‐assisted degradation of dye from water. (30th October 2017) - Tong, Xiaowen; Yang, Zhiquan; Feng, Jinna; Li, Ying; Zhang, Hongguo
Abstract : Semiconductor‐based photocatalysis is an environmental friendly and cost‐effective technique for water treatment. Due to their unique properties, metal–organic frameworks (MOFs) are considered as ideal platform to develop composite photocatalyst. In this study, Bismuth oxychloride (BiOCl) was first attempt to be incorporated with highly stable MOFs, UiO‐66(Zr) by hydrothermal reaction. Different characterization methods including X‐ray diffraction, Scanning electron microscopy, Fourier transform infrared spectroscope, X‐ray photoelectron spectroscopy had been used to prove the successful synthesis of composite photocatalyst. The resultant BiOCl/UiO‐66 composite showed higher photodegradation performance of Rhodamine B (RhB) under ultraviolet and visible light irradiation than that of pristine materials and their mechanically mixed sample. In addition, the composite exhibited good structural stability and reusability. The photocatalytic mechanism of RhB degradation over the composite under visible light proceeded via a photosensitization process. A better adsorptivity of RhB and effective electron transfer within the hybrid material might be responsible for the enhanced photocatalytic performance. Abstract : BiOCl and UiO‐66(Zr) were combined together through chemical bonds (C‐Cl), and a different morphology compared to pristine material was obtained in the preparation process, which brought a better adsorptivity of RhB and effective electron transfer within the hybrid material. The BiOCl/UiO‐66(Zr) composite shows prior photosensitization degradation performance for RhB under visible light than pristine materials.